PENGARUH RETURN ON ASSET (ROA), CAPITAL ADEQUACY RATIO (CAR), NON-PERFORMING FINANCING (NPF) DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP PENYALURAN PEMBIAYAAN BANK UMUM SYARIAH DI INDONESIA PERIODE 2015-2019 - Priyo Wicaksono; Haerudin Haerudin (Value Added : Majalah Ekonomi dan Bisnis, 2021)
Currently, Islamic Commercial Banks continue to show positive growth. In2019, the resilience of Islamic Commercial Banks is increasingly solid. This studyaims to determine the effect of ROA, CAR, NPF and BOPO on the distribution offinancing to Indonesian Islamic commercial banks in 2015-2019. This research isa quantitative research.The population and sample selected using a non-probability samplingmethod and included in the saturated sample, namely the entire sample as many as14 Islamic commercial banks. The results of data analysis indicate that ROA andNPF has a positif effect on financing distribution with a significance of 5,2% forROA and 43% for NPF. Then CAR had a negative effect on financing distributionwith a significance of 0,02%, while BOPO have a negative effect on financingdistribution with a significance of 86%